Factors Influencing Customer’s Acceptance of Islamic Banking Products and Services - Latip, Malisah; Yahya, M.H.; Junaina, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2017)
The emergence of Islamic banking system has had a huge impact on the financial industry. This research attempts to identify the influential factors that are associated with Islamic banking adoption between the Muslim and non-Muslim populations in Sarawak, Malaysia. With the “adoption of Islamic banking” as the dependent variable, this study studies its relationship with seven independent variables. They are, four attributes of innovation, namely; 1) relative advantage, 2) compatibility, 3) observability and 4) complexity, and three additional variables namely; 5) perceived risk, 6) perceived trust and 7) customer innovativeness. A convenient sampling method is used whereby a questionnaire is administered to 436 respondents in Sarawak, Malaysia. Using the logistic regression method, three factors; 1) compatibility, 2) relative advantage/observability and 3) complexity are found to have significant relationship with customers’ adoption of Islamic banking products and services.